THE IMPACTS OF UNCLEAR LAW AND BORDER ON ENVIRONMENTAL PROTECTION: THE CASE OF THE MANGGARAI TIMUR AND NGADA REGENCIES OF FLORES, INDONESIA - Any Andjarwati; Ananda Prima Yurista; Fajri Matahati Muhammadin (Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractThe land of Manggarai Timur and Ngada in Flores, Indonesia, is facing complexities in the agrarian sector. There is an overlap of laws on land tenure in the border area between the regencies based on the Regional Spatial Plans of both Manggarai Timur and Ngadha regencies. Not only that this creates horizontal conflicts between the peoples, but the overlap of mining policies also affects the environment. This research investigates the problems and discovers that the complexity can only be untangled by creating a ‘Strategic Area’ which can be implemented with a reconstruction of the current system of spatial planning law. IntisariTanah Manggarai Timur dan Ngada di Flores, Indonesia, menghadapi kompleksitas serius di sektor agraris. Ada tumpang tindih hukum tentang kepemilikan lahan di daerah perbatasan antar kabupaten berdasarkan Rencana Tata Ruang Wilayah Kabupaten Manggarai Timur dan Ngadha. Hal ini menyebabkan konflik horizontal antara masyarakat. Selain itu, tumpang tindih kebijakan terkait pertambangan juga mempengaruhi lingkungan. Penelitian ini menyelidiki masalah dan menemukan bahwa kompleksitasnya hanya dapat dilepaskan dengan menciptakan 'Kawasan Strategis' yang hanya dapat diimplementasikan dengan adanya rekonstruksi terhadap sistem hukum penataan ruang saat ini.